2017
DOI: 10.1371/journal.pone.0176777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shenmai injection on preventing the development of nitroglycerin-induced tolerance in rats

Abstract: Long-term nitroglycerin (NTG) therapy causes tolerance to its effects attributing to increased oxidative stress and endothelial dysfunction. Shenmai injection (SMI), which is clinically used to treat cardiovascular diseases, consists of two herbal medicines, Ginseng Rubra and Ophiopogonjaponicas, and is reported to have antioxidant effects. The present study was designed to investigate the potential preventive effects of Shenmai injection on development of nitroglycerin-induced tolerance. The present study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The mechanisms underlying reperfusion injury are complex and multifactorial, with ROS generation, Ca 2+ overload, opening of the mPTP, endothelial dysfunction and pronounced inflammatory responses all implicated in causing the damage (31). Radix Ginseng Rubra, Radix Ophiopogonis and S. miltiorrhiza Bunge, which are included in YYH, have been investigated to determine their potential combined pharmaceutical properties, including anti-inflammatory, anti-oxidant, microcirculation promotion and cardioprotective abilities (32,33). In the clinic, it has been reported that YYH improved myocardial reperfusion injury following PCI in patients with acute myocardial infarction (18).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying reperfusion injury are complex and multifactorial, with ROS generation, Ca 2+ overload, opening of the mPTP, endothelial dysfunction and pronounced inflammatory responses all implicated in causing the damage (31). Radix Ginseng Rubra, Radix Ophiopogonis and S. miltiorrhiza Bunge, which are included in YYH, have been investigated to determine their potential combined pharmaceutical properties, including anti-inflammatory, anti-oxidant, microcirculation promotion and cardioprotective abilities (32,33). In the clinic, it has been reported that YYH improved myocardial reperfusion injury following PCI in patients with acute myocardial infarction (18).…”
Section: Discussionmentioning
confidence: 99%
“…SMI is widely used for the treatment of atherosclerotic coronary heart disease and chronic pulmonary heart disease in China (Li et al 2011). SMI has high antioxidant activity and anticancer effects, balances blood pressure, and eliminates surplus free radicals (Yu et al 2014;Shi et al 2015;Zhou et al 2017). Nevertheless, there were few reports that ginsenosides could reverse MDR except 20(S)-Rh 2 (Zhang et al 2012a(Zhang et al , 2012b.…”
Section: Introductionmentioning
confidence: 99%
“…Shenmai injection (SMI) is an injection-based on traditional Chinese medicine; it contains traditional Chinese remedy extracts Ophiopogonjaponicas (lilia-ceae), and Ginseng Rubra (araliaceae) [11] and is widely used to clinically treat heart diseases, sepsis, osteoarthritis and asthma [12][13][14][15]. The toxicity of SMI has been evaluated and is generally considered to be safe to use [16,17].…”
Section: Introductionmentioning
confidence: 99%